The role of training and development, employee engagement in work performance: organizational commitment as a mediator - Hosen, Sharif; Hamzah, Siti Raba'ah; Ismail, Ismi Arif; Alias, Siti Noormi; Abd Aziz, Mohd Faiq (Journal of Entrepreneurship, Business and Economics, 2024)
The hotel sector is a significant pillar in Bangladesh because it has significantly contributed to its economic development. Employee work performance has become a global business phenomenon in the service industry over various years because work performance in the hotel industry heavily depends on employee engagement and training facilities. The present research determined the mediating influence of organizational commitment on the impact of training and development and employee engagement on work performance among frontline employees in Bangladesh. Applying a simple random technique, from the 362 frontline employees, data was gathered from the selected population. Collected data was analyzed using SPSS, which was used for descriptive analysis, and Smart-PLS 3.0 was applied to the structure and measurement models. The structure model tested all hypotheses of this study. In this study, training and development, employee engagement, and organizational commitment significantly influence work performance. Moreover, organizational commitment partially mediates the impact of training and development and employee engagement on work performance. The contribution is that owners, managers, and policymakers should take necessary action to develop work performance and organizational commitment, considering the right behaviour. Additionally, employee engagement and development training facilities should be implemented to meet the hotel's demands for the future and present. The present study explains outcomes with various research limitations that suggest further study is needed. This study fulfils the research gaps in the hotel sector of Bangladesh, which indicates that organizational commitment, work performance, employee engagement, training and development were not high. Research Paper Keywords: Training and Development, Employee Engagement, Organisational Commitment, Work Performance, Frontline Employees Reference to this paper should be made as follows: Hosen, S., Hamzah, S.R., Ismail, I.A., Alias, S.N., & Abd Aziz, M.F. (2024). The role of training and development, employee engagement in work performance: organizational commitment as a mediator. Journal of Entrepreneurship, Business and Economics , 12 (2), 28–68.